Low Pathogenic Avian Influenza: A Permanent Threat to Poultry Farming in Africa - (:unkn) unknown (My University, 2022)
Initially isolated from turkey flocks in Wisconsin in America in 1966, the avian influenza virus H9N2 has become a serious threat not only to the avian industry but also to human health. Since the 90s, the virus spread in chicken flocks in several countries, starting with China in 1992, then in many parts of Asia, the Middle East, and North Africa. Actually, the LPAI H9N2 subtype is believed to be one of the main causes of chicken respiratory diseases in Africa. Since the first introduction of AIV H9N2 in Morocco in 2016, the virus became enzootic and causes outbreaks in different parts of the country. The intensive uses of inactivated vaccines were insufficient to eradicate the disease, which affects intermittently poultry flocks in different parts of the country at different periods with different degrees of severities, depending on concomitant diseases, management, and other environmental factors. The objective of this chapter will be to explain the H9N2 infection with regard to both animal and human health in Africa and to highlight the assessment of African strategies for control of LPAI in poultry.
Keywords: African Research